Pengaruh Intervensi Apoteker terhadap Pengetahuan, Tingkat Kepuasan dan Outcome Terapi Pasien Swamedikasi Commond Cold di Apotek Kasih Agape - Tarigan, Eunike Victorita; Wiryanto, Wiryanto; Dalimunthe, Aminah (Journal of Pharmaceutical and Sciences, 2025)
Self-medication for minor illnesses such as the common cold is generally done by the community. In situations like this, the role of pharmacists is very important in providing education to improve patient safety. This study aims to analyze the effect of pharmacist intervention (pretest-posttest) on the level of knowledge and outcome of self-medication therapy for common cold patients at Kasih Agape Pharmacy Medan. This study used a quasi-experimental design with a one-group pretest-posttest design approach on the knowledge and outcome indicators, while the patient satisfaction indicator used a descriptive quantitative research design. The sample consisted of 50 patients who were in the intervention group (pretest-posttest), randomly selected using a purposive sampling technique. The intervention was given in the form of pharmacist education and counseling. Data were collected using a questionnaire that had been tested for validity and reliability. The results of the analysis showed that there was a significant increase in the level of knowledge (p <0.05) and outcome of therapy (p <0.05) in the intervention group compared to the pretest and posttest. These results can also be seen as increasing patient knowledge, and the outcome of therapy can have an impact on increasing patient satisfaction. This study shows that pharmacist intervention can effectively improve the quality of self-medication for the common cold in patients. This study emphasizes the importance of the active role of pharmacists in providing education to support safe, rational drug use and improve therapeutic outcomes.